2022
DOI: 10.1182/bloodadvances.2021006591
|View full text |Cite
|
Sign up to set email alerts
|

A single administration of hIL-7-hyFc induces long-lasting T-cell expansion with maintained effector functions

Abstract: Interleukin-7 (IL-7) is an essential cytokine for T-cell homeostatic proliferation and maintenance. Clinical studies have shown the potential benefits of IL-7 therapy in various diseases associated with lymphopenia. However, the kinetics of the T-cell response to a single administration of IL-7 in humans have not been fully elucidated. Here, we investigated the effects of Fc-fused long-acting recombinant human IL-7 (hIL-7-hyFc, efineptakin alfa) on lymphocytes in healthy adults after a single subcutaneous or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The rhIL-7 treatment led to increases in CD4 + T cells in both peripheral blood and tissues. Regarding the newer drug Efineptakin-α, administration in healthy adults induced a sustained increase in the numbers of naïve, T CM , T EM and T EMRA CD4 + and CD8 + T cells without qualitative changes ( Kim et al, 2022 ). The authors concluded that hIL-7-hyFc is a potential treatment for patients with compromised T-cell immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The rhIL-7 treatment led to increases in CD4 + T cells in both peripheral blood and tissues. Regarding the newer drug Efineptakin-α, administration in healthy adults induced a sustained increase in the numbers of naïve, T CM , T EM and T EMRA CD4 + and CD8 + T cells without qualitative changes ( Kim et al, 2022 ). The authors concluded that hIL-7-hyFc is a potential treatment for patients with compromised T-cell immunity.…”
Section: Discussionmentioning
confidence: 99%
“… 16 A recombinant human interlukin-7 (IL-7) with an extended half-life (rhIL-7-hyFc; efineptakin α) significantly increased expansion of T cells in patients with cancer and healthy volunteers. 17 , 18 Our group demonstrated that mice with tumor engraftment treated with CAR-Ts plus rhIL-7-hyFc had dramatic expansion of CAR-Ts and significantly better tumor control than CAR-T–treated mice. 19 These studies provided rational for an ongoing clinical trial combining rhIL-7-hyFc and CD19 CAR-Ts in patients with relapsed/refractory large B-cell lymphoma (NCT05075603).…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, it was designed to minimize the loss of the bioactivity of drug candidates and prevent ADCC- or CDC-mediated cell killing effects. Notably, NT-I7 enhances T-cell-mediated antitumor immunity through multiple mechanisms, including expansion of the TCR repertoire; sensitization of T cells to weaker antigens; boosting naïve T cells, stem cell-like memory T cells (T SCM ) and memory T cells; promotion of memory T-cell differentiation; enhancement of T-cell trafficking and infiltration into tumors; augmentation of the antigen-specific T-cell response; antagonization of T-cell exhaustion and other inhibitory networks; and stimulation of the proinflammatory cytokine milieu in the TME ( 113 ).…”
Section: Il-7mentioning
confidence: 99%